THE IMPACT OF SUKUK ON ECONOMIC GROWTH IN COUNTRIES WITH THE HIGHEST SUKUK ISSUANCE: A CASE STUDY OF TURKEY - Putri, Mina Aissyawa Sunarto; Munawar, Wildan (Jurnal Syarikah : Jurnal Ekonomi Islam, 2025)
Sukuk is a sharia-based investment instrument that has made an important contribution to the country's economy. This study aims to analyze the impact of sukuk issuance on economic growth in the five countries with the largest sukuk issuance. The research approach uses a descriptive quantitative method with time series data and Vector Error Correction Model (VECM) analysis to assess the short-term and long-term relationship between sukuk and economic growth. The secondary data used covers the period 2014–2023. The results of the analysis at the individual level show a probability value above the minimum level, which means that the partial effect of sukuk is not yet statistically significant on Turkey's GDP. This could be due to internal factors, such as pressure from domestic instability, geopolitical tensions, and a current account deficit of USD 32.6 billion in 2016.